CULTURAL HERITAGE AND THE CLIMATE CRISIS: A LITERATURE REVIEW - Ernestina Rita Meira Engel; Lisiane Ilha Librelotto (Mix Sustentável)
Extreme weather events have been increasing over time. In this way, climate change represents obstacles to society, imposing challenges on cities. Among them is the preservation of their cultural and natural heritage. Urban complexes with a preservation interest face greater vulnerability due to natural, cultural and social factors. In this context, the aim of this article is to present the state of the art on research into the impacts of climatic events on sites of preservation interest. The methodological procedures comprised four stages: defining the topic and research question; searching academic databases; establishing inclusion and exclusion criteria; and analyzing the materials. The research found shows a consensus on the need to pay attention to the impacts of climate change on cultural and natural heritage. As limitations, most of the research with case studies focuses on the Global North. In terms of gaps, the research highlights the need for an integrative approach to the preservation of cultural heritage in the face of the impacts of climate change.